Lactobacillus Modulates Chlamydia Infectivity and Genital Tract Pathology in vitro and in vivo - Chen, Hongliang; Min, Shuling; Wang, Li; Zhao, Lanhua; Luo, Fangzhen; Lei, Wenbo; Wen, Yating; Luo, Lipei; Zhou, Qianting; Peng, Lixiu; Li, Zhongyu (Frontiers in Microbiology, 2022)
Since we previously reported that women with Chlamydia trachomatis infection resulted in a significant overall reduction in Lactobacillus in the vagina, the interactions between the altered Lactobacillus and C. trachomatis, on the other hand, are unknown. Here, we employed both in vitro and in vivo models to evaluate the effects of these changed Lactobacillus on Chlamydia infection. We found that Lactobacillus iners, Lactobacillus crispatus, Lactobacillus jensenii, Lactobacillus salivarius, Lactobacillus gasseri, Lactobacillus mucosae, and Lactobacillus reuteri all significantly reduced C. trachomatis infection in a dose- and time-dependent manner. The strongest anti-Chlamydia effects was found in L. crispatus (90 percent reduction), whereas the poorest was found in L. iners (50 percent reduction). D (-) lactic acid was the key component in Lactobacillus cell-free supernatants (CFS) to inactivate Chlamydia EBs, showing a positive correlation with the anti-Chlamydia activity. The effects of D (-) lactic acid were substantially abolished by neutralizing the pH value to 7.0. In vivo, mice intravaginally inoculated with Lactobacillus mixtures (L. crispatus, L. reuteri and L. iners at a ratio of 1:1:1), but not single Lactobacillus, after genital Chlamydia infection, significantly attenuated the levels of Chlamydia live organism shedding in both the lower genital tract and intestinal tract, reduced cytokines production (TNF-α, IFN-γ and IL-1β) in the vagina, and eased the Chlamydia pathogenicity in the upper genital tract. Taken together, these data demonstrate that Lactobacillus inhibits Chlamydia infectivity both in vivo and in vitro, providing useful information for the development of Lactobacillus as therapeutic agents to cure Chlamydia infection.